Current role of selective internal radiation with yttrium-90 in liver tumors. (May 2016) - Lau, Wan Yee; Teoh, Yee Leong; Win, Khin Maung; Lee, Rheun-Chuan; de Villa, Vanessa H; Kim, Yun Hwan Joseph; Liang, Po-Chin; Santos-Ocampo, Ramon S; Lo, Richard Hoau Gong; Lim, Kieron Boon Leng; Tai, David Wai Meng; Ng, David Chee Eng; et al.
An expert panel met to review the evidence for selective internal radiation therapy (SIRT) using yttrium-90 microspheres in hepatocellular carcinoma and metastases from colorectal cancer and neuroendocrine tumors. There is now convincing evidence for the safety and efficacy of SIRT in these situations albeit mostly from retrospective cohort studies. There are a number of ongoing prospective randomized controlled clinical trials investigating the role of SIRT in liver tumors; however, data from these trials are still several years away (although the SIRFLOX study has been recently published). In this evolving environment, published evidence and the authors' experience were used to summarize the current and potential role of SIRT in the management of hepatocellular carcinoma of intermediate or advanced stage and in liver-dominant metastatic colorectal cancer and metastatic neuroendocrine tumors.